2008
DOI: 10.1002/aoc.1441
|View full text |Cite
|
Sign up to set email alerts
|

Tin dithiocarbamates: applications and structures

Abstract: The uses and potential utility of tin/organotin dithiocarbamate, − S 2 CNR 2 , compounds are reviewed. Various derivatives exhibit exciting potential as anti-cancer agents, anti-microbial agents and insecticides, e.g. against mosquito larvae. Tin dithiocarbamates have also proven useful as precursors for tin sulfide nanoparticles. There is a wealth of structural data available for such compounds and with the exception of the diorganotin bis(dithiocarbamate) compounds, R 2 Sn(S 2 CNR 2 ) 2 , compounds for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
153
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(173 citation statements)
references
References 120 publications
13
153
0
1
Order By: Relevance
“…The motivation for the present study arose from recent observations of remarkable antimicrobial activities, specifically against Gram-positive bacteria, exhibited by related phosphanegold(I) thiocarbamate compounds, i.e. Ph 3 PAu[SC(OR)=N(tol-p)], for R = Me, Et and iPr [29], and by the knowledge that other metal dithiocarbamates have been reported to exhibit antimicrobial activity [30][31][32].…”
Section: Chemistrymentioning
confidence: 99%
“…The motivation for the present study arose from recent observations of remarkable antimicrobial activities, specifically against Gram-positive bacteria, exhibited by related phosphanegold(I) thiocarbamate compounds, i.e. Ph 3 PAu[SC(OR)=N(tol-p)], for R = Me, Et and iPr [29], and by the knowledge that other metal dithiocarbamates have been reported to exhibit antimicrobial activity [30][31][32].…”
Section: Chemistrymentioning
confidence: 99%
“…15,18 If carboxylic functions are the terminal groups of SAMs, they can be used to covalently immobilize compounds with amine groups after an activation process, such as with N-hydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC). 19,20 Dithiocarbamates (DTCs) which have been commonly used as chelating ligands in coordination chemistry monolayers 21 provide an alternative to alkanethiol SAMs for gold surface modification. 22,23 The major structural characteristic of DTC is the resonance structure among N−C−S 2 , including both the sulfur−carbon bond and the carbon−nitrogen bond due to the free electron pairs on the sulfur and nitrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Two comprehensive reviews on the structural aspects of organotin carboxylates have been published. [8,9] Organotin carboxylates adopt structures, which are dependent on both the nature of the alkyl (or aryl) substituent bound to the tin atom and on the type of the carboxylate ligand. Crystallographic studies of the dicarboxylato tetraorganostannoxanes, of formula {[R 2 Sn(O 2 CR )] 2 O} 2 , have shown that there are at least five distinct types of structure known for them.…”
Section: Introductionmentioning
confidence: 99%